Imaging in Nontraumatic Pediatric Head and Neck Emergencies - Ellika, Shehanaz K.; Chadha, Meghna; Yang, Zhiyun (Journal of Pediatric Neurology, 2017)
Pediatric patients often present to the emergency department with a wide variety of infectious, inflammatory, and neoplastic lesions of the head and neck. Evaluation of pediatric patients in the emergency setting is complicated by limited history and physical examination. Imaging plays an important role in arriving at an accurate diagnosis. The fascial spaces and compartments of the neck provide an approach to differential diagnosis, and knowledge of the typical clinical and imaging manifestations of common pediatric head and neck emergencies allows the radiologist to identify the condition and associated complications that may require emergent surgical management. Computed tomography (CT) is the first-line imaging modality in the emergency setting; however, magnetic resonance imaging (MRI) plays an important secondary role.
Keywords: head and neck infection; head and neck imaging; pediatrics